Histologic Correlates of Clinical and Endoscopic Severity in Children Newly Diagnosed With Ulcerative Colitis. (November 2017) - Boyle, Brendan; Collins, Margaret H.; Wang, Zhu; Mack, David; Griffiths, Anne; Sauer, Cary; Markowitz, James; LeLeiko, Neal; Keljo, David; Rosh, Joel; Baker, Susan S.; Pfefferkorn, Marian; et al.
Abstract : To characterize rectal histology in an inception cohort of children newly diagnosed with ulcerative colitis (UC) and to explore its relationship with clinical indices of disease severity. The PROTECT (Predicting Response to Standardized Pediatric Colitis Therapy) Study enrolled children 17 years of age and younger newly diagnosed with UC. Baseline rectal biopsies were evaluated for acute and chronic inflammation, eosinophilic inflammation (peak eosinophil count > 32 eosinophils/high powered field, eosinophilic cryptitis or abscesses), and architectural/nonarchitectural chronic changes. Correlation with clinical indices including Mayo endoscopy subscore and Pediatric Ulcerative Colitis Activity Index was performed. Rectal biopsies from 369 patients (mean age, 12.9±3.1 y, 50% female) were reviewed. Cryptitis was found in 89%, crypt abscesses in 25%, and eosinophilic inflammation in 58%. Crypt distortion/atrophy was present in 98% of specimens. Higher grades of acute and chronic inflammation were associated with the presence of basal plasmacytosis ( P <0.0001), basal lymphoid aggregates ( P <0.0001), and surface villiform changes ( P <0.0001). A severe Mayo endoscopy subscore was most common among those with severe acute and chronic inflammation, although this relationship was not linear. Severe Pediatric Ulcerative Colitis Activity Index scores were associated with the absence of or only mild eosinophilic inflammation (<32 eosinophils/high powered field) ( P <0.03) and the presence of surface villiform changes ( P <0.005). Acute and chronic inflammation, eosinophilic inflammation and chronic changes are common in children newly diagnosed with UC. The clinical and biological implication of low to absent eosinophilic inflammation and the presence of surface villiform changes requires further study.